Powerful mechanical-driven outflows in the central parsecs of the low-luminosity active galactic nucleus ESO 428-G14. (25th August 2018) - May, D; Rodríguez-Ardila, A; Prieto, M A; Fernández-Ontiveros, J A; Diaz, Y; Mazzalay, X
ABSTRACT: Low-luminosity Active Galactic Nuclei (LLAGNs) are characterized for low-radiative efficiency, much less than one percent of their Eddington limit. Nevertheless, their main energy release may be mechanical, opposite to powerful AGN classes like Seyfert and Quasars. This work reports on the jet-driven mechanical energy and the corresponding mass outflow deposited by the jet in the central 170 parsecs of the nearby LLAGN ESO 428-G14. The jet kinetic output is traced through the coronal line [Si vi ] λ19641 Å. It is shown that its radial extension, up to hundreds of parsecs, requires a combination of photoionization by the central source and shock excitation as its origin. From the energetics of the ionized gas it is found that the mass outflow rate of the coronal gas is in the range from 3–8 M⊙ yr −1, comparable to those estimated from H i gas at kiloparsec scales in powerful radio galaxies.